1982
DOI: 10.17016/ifdp.1982.204
|View full text |Cite
|
Sign up to set email alerts
|

The Out-of-Sample Failure of Empirical Exchange Rate Models: Sampling Error or Misspecification?

Abstract: A companion study (Meese and Rogoff 1983) compared the out-ofsample fit of various structural and time-series exchange rate models and finds that the random walk model 1 performs as well as any estimated model at one-to twelve-month horizons for 1970s dollar/mark, dollar/pound, dollar /yen, and trade-weighted dollar exchange rates. 2 The structural models perform poorly even though their forecasts are purged of all uncertainty concerning the future paths of their explanatory variables by using actual realized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
0
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(128 citation statements)
references
References 25 publications
(33 reference statements)
7
118
0
3
Order By: Relevance
“…35. The classic reference is Messe and Rogoff (1983). Of course, exchange-rate models are not the only disappointing ones.…”
Section: Notesmentioning
confidence: 99%
“…35. The classic reference is Messe and Rogoff (1983). Of course, exchange-rate models are not the only disappointing ones.…”
Section: Notesmentioning
confidence: 99%
“…Given our relatively successful empirical estimates of the model coefficients, we also conduct both an in-sample and out-of-sample forecasting analysis to see if the model has any useful forecasting ability in comparison to the Random Walk forecast made famous by Rogoff (1983a, 1983b). To do this, we look at four possible models encompassed by Equation (25): 1st Model: le t = Ω + δ 1 lM t + δ 2 lM * t + δ 3 li H t + δ 4 i * t + δ 5 ly t + δ 6 ly * t .…”
Section: In-sample and Out-of-sample Forecasting Performancementioning
confidence: 99%
“…The original popular models used to determine and forecast the nominal exchange rates include the flexible price monetary models such as Frenkel and Johnson (1976), Musa (1976), and Bilson (1978a and1978b). The early tests of the monetary models using traditional econometric procedures were not particularly favorable either in terms of significance of the coefficients or in their in-sample or out-of-sample ability to forecast exchange rates, as shown by Rogoff (1983a, 1983b) who showed that exchange rate models fail to outperform a simple random walk. The early tests of the monetary models using traditional econometric procedures were not particularly favorable either in terms of significance of the coefficients or in their in-sample or out-of-sample ability to forecast exchange rates, as shown by Rogoff (1983a, 1983b) who showed that exchange rate models fail to outperform a simple random walk.…”
Section: Introductionmentioning
confidence: 99%
“…In the seminal paper by Meese and Rogoff (1983a,b), the authors find that the random walk model can outperform all of the exchange rate models of the seventies in the out‐of‐sample fit. The failure to find evidence connecting economic models to the exchange rate has inspired subsequent researchers to analyse the robustness of these findings based on different samples, model specifications and explanatory variables.…”
Section: Introductionmentioning
confidence: 99%